Ghost Plane : The Inside Story of the CIA's Secret Rendition Programme - Grey, Stephen (London Hurst & Company, 2006)
In December 2005 Condoleezza Rice, the US Secretary of State, assured the world that the flights of CIA private jets that have criss-crossed Europe since 9/11 had no role in sending prisoners to be tortured.
Include Appendix, Note and Index
Keywords: Torture -- Intelligence service -- United States -- United States. Central Intelligence Agency